Nurse‐led educational interventions on cancer pain outcomes for oncology outpatients: a systematic review. (25th February 2015) - Zhou, L.; Liu, X.‐L.; Tan, J.‐Y.; Yu, H.‐P.; Pratt, J.; Peng, Y.‐Q.
<x xml:space="preserve">Abstract</x> Background Cancer pain management is still unsatisfactory, although some effective guidelines exist. Educational interventions are reported to be useful in pain relief for oncology outpatients. Aim The aims of this systematic review were to evaluate the effects of nurse‐led educational interventions on improving cancer pain outcomes for oncology patients, and to establish an effective cancer pain protocol for clinical nursing practice in China. Methods A three‐step search strategy was utilized. Eight databases were searched using the standards provided by the Joanna Briggs Institute that guided article selection, critical appraisal, data collection and data synthesis. Results A total of 1093 studies were identified through a literature search. Only six studies complied with the inclusion criteria and were found to be methodologically sound. In general, the included studies indicated positive results pertaining to patient's knowledge and attitudes towards analgesics and cancer pain management and decreased pain intensity. Studies reported minimal effects of intervention on anxiety, depression, satisfaction regarding cancer pain management and patient's quality of life. Conclusions Educational interventions were reported as effective methods to improve cancer pain outcomes. Analysis of the six included studies demonstrated the overall positive effects of nurse‐led educational interventions for improving cancer pain management. Implications for nursing and health policy The results suggest that an effective cancer pain protocol for improving cancer pain management can be established in China.